Technological Pedagogical Content Knowledge (TPACK) in pre-service and in-service chemistry teacher training: a systematic literature review - Severo Bernardes, Thaygra; Serrano de Andrade Neto, Agostinho (RENOTE, 2021)
To guide the integration of Information and Communication Technologies (ICT) in the classroom, the theoretical model Technological Pedagogical Content Knowledge (TPACK), proposed by Mishra and Koehler in 2006, reinforces the importance of connecting pedagogical, technological, and content knowledge of teachers. This research sought to investigate the literature on how the theoretical model TPACK is being used for the integration of technology in Chemistry teaching. This investigation was based on a Systematic Literature Review (SLR), reaching a sample of 23 articles published in scientific journals from 2006 to 2019. In general, the researches that composed this SLR uses the theoretical model TPACK in a more theoretical way and mostly in in-service teacher training. The lack of research in the Brazilian context signals the need for more work supported by this framework, which can lead to practices that are more aligned with the contemporary needs of Chemistry teacher training.